2016
DOI: 10.1093/cercor/bhw266
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Spatiotemporal Response Properties of Excitatory Versus Inhibitory Neurons in the Mouse Auditory Cortex

Abstract: In the auditory system, early neural stations such as brain stem are characterized by strict tonotopy, which is used to deconstruct sounds to their basic frequencies. But higher along the auditory hierarchy, as early as primary auditory cortex (A1), tonotopy starts breaking down at local circuits. Here, we studied the response properties of both excitatory and inhibitory neurons in the auditory cortex of anesthetized mice. We used in vivo two photon-targeted cell-attached recordings from identified parvalbumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 78 publications
9
44
1
Order By: Relevance
“…Initial studies using synthetic dyes in anesthetized animals described a local heterogeneous frequency preference (Bandyopadhyay et al, 2010;Rothschild et al, 2010) in L2/3. These results in L2/3 have been confirmed using the sensitive synthetic dye Cal-520 (Li et al, 2017;Tischbirek et al, 2019;Zeng et al, 2019) in anesthetized and awake mice and rats, with the ultrasensitive genetically encoded calcium indicator (GECIs) GCaMP6s in awake mice (Meng et al, 2017;Liu et al, 2019), as well as by in vivo patch clamp studies (Maor et al, 2016). In addition to primary auditory cortex, L2/3 of ACX areas such as the anterior auditory field and secondary ACX were also shown to contain fractured tonotopic organization (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…Initial studies using synthetic dyes in anesthetized animals described a local heterogeneous frequency preference (Bandyopadhyay et al, 2010;Rothschild et al, 2010) in L2/3. These results in L2/3 have been confirmed using the sensitive synthetic dye Cal-520 (Li et al, 2017;Tischbirek et al, 2019;Zeng et al, 2019) in anesthetized and awake mice and rats, with the ultrasensitive genetically encoded calcium indicator (GECIs) GCaMP6s in awake mice (Meng et al, 2017;Liu et al, 2019), as well as by in vivo patch clamp studies (Maor et al, 2016). In addition to primary auditory cortex, L2/3 of ACX areas such as the anterior auditory field and secondary ACX were also shown to contain fractured tonotopic organization (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…Such diversity has also been reported for neurons across different laminar locations within the same cortical column (Abeles and Goldstein, 1970; Sakata and Harris, 2009; Sugimoto et al, 1997; Wallace and Palmer, 2008). Recent two-photon calcium imaging and visually guided loose-patch recording studies (Bandyopadhyay et al, 2010; Maor et al, 2016; Rothschild et al, 2010; Winkowski and Kanold, 2013) have reported that BF of even nearby neurons can be quite heterogeneous, and that such local heterogeneity is much more pronounced in superficial than in middle layers (Winkowski and Kanold, 2013). The abovementioned studies were mostly carried out in the primary visual cortex (A1).…”
Section: Introductionmentioning
confidence: 99%
“…For imaging and recording, a custom-made metal pin was glued to the 176 skull using dental cement and connected to a custom stage to allow precise positioning of the 177 head relative to the speaker (facing the right ear). The muscle overlying the left auditory cortex was removed, and a craniotomy (∼2 × 2 mm) was performed over A1 (coordinates, 2.3 mm 179 posterior and 4.2 mm lateral to bregma) as described previously [38][39][40] . 180 181…”
Section: Surgical Procedures 170mentioning
confidence: 99%
“…Cell-attached recordings were obtained using targeted patch-clamp recording by a previously 183 described procedure [40][41][42] . For visualization, the electrode was filled with a green fluorescent dye 184 (Alexa Flour-488; 50 μM).…”
Section: Imaging and Electrophysiology 182mentioning
confidence: 99%
See 1 more Smart Citation